Filter paper method of soil suction measurement - Bicalho, Kátia Vanessa (2007)
The capillary pressure of the soil (i.e., the pressure difference between air and water components in soil voids) is a key variable in the analysis of the hydro-mechanical behavior of unsaturated soils. Therefore a simple and economical laboratory method for the measurement of the capillary pressure of the soil (also known as soil matric suction, the reference being the atmospheric pressure), even if a degree of approximation is involved, is of considerable value. The filter paper method calculates soil suction indirectly by measuring the gravimetric water content of the filter paper at equilibrium that is related to soil suction through a predetermined calibration curve. The advantages of the method are simplicity, economy and reasonable accuracy. It can be used to measure suctions from 10 to 30000 kPa. In this paper, the authors use the contact filter paper method for matric suction measurements of an unsaturated compacted silty sand (formed by the weathering of granite) which has been used as a building material for a road in the north of Portugal. The matric suctions inferred from filter paper measurements depend on the calibration between the water content of the filter paper and suction. Therefore, three calibration curves proposed at the literature (Chandler et al. 1992; ASTM D 5298; and Oliveira & Marinho 2006) for the Whatman 42 filter paper are used to interpret the measured filter paper gravimetric water contents. The results of these tests are compared to other techniques (i.e., tensiometers, and the osmotic technique) used to measure or control the negative pore water pressure in the compacted soil specimens and the results obtained are reasonably accurate.